Effect of high dose vitamin D3 on the HIV-1 reservoir: A pilot randomised controlled trial - Matthew C. Pitman; Niamh Meagher; David J. Price; Ajantha Rhodes; J. Judy Chang; Barbara Scher; Brent Allan; Alan Street; James H. McMahon; Thomas A. Rasmussen; Paul U. Cameron; Jennifer F. Hoy; et al. (Elsevier, 2023)
Introduction: Antiretroviral therapy for people living with HIV-1 must be taken lifelong due to the persistence of latent virus in long-lived and proliferating CD4+ T cells. Vitamin D3 is a steroidal gene transcription regulator which exerts diverse effects on immune and epithelial cells including reductions in CD4+ T cell proliferation and improvement in gut barrier integrity. We hypothesised that a high dose of vitamin D3 would reduce the size of the HIV-1 reservoir by reducing CD4+ T cell proliferation. Methods: We performed a randomised placebo-controlled trial evaluating the effect of 24 weeks of vitamin D3 (10,000 international units per day) on the HIV-1 reservoir and immunologic parameters in 30 adults on antiretroviral therapy; participants were followed for 12 weeks post-treatment. The primary endpoint was the effect on total HIV-1 DNA at week 24. Parameters were assessed using mixed-effects models. Results: We found no effect of vitamin D3 on the change in total HIV-1 DNA from week 0 to week 24 relative to placebo. There were also no changes in integrated HIV-1 DNA, 2-long-terminal repeat (2-LTR) circles or cell-associated HIV-1 RNA. Vitamin D3 induced a significant increase in the proportion of central memory CD4+ and CD8+ T cells, a reduction in the proportion of senescent CD8+ T cells and a reduction in the natural killer cell frequency at all time points including week 36, 12 weeks after the study drug cessation. At week 36, there was a significant reduction in total HIV-1 DNA relative to placebo and persistently elevated 25-hydroxyvitamin D levels. No significant safety issues were identified. Conclusions: Vitamin D3 administration had a significant impact on the T cell differentiation but overall effects on the HIV-1 reservoir were limited and a reduction in HIV-1 DNA was only seen following cessation of the study drug. Additional studies are required to determine whether the dose and duration of vitamin D3 can be optimised to promote a continued depletion of the HIV-1 reservoir over time. Trial registration: ClinicalTrials.gov NCT03426592.